The impact of the early tenotomy of Achilles tendon on the length and results of congenital clubfoot severe forms treatment - Rakonjac , Zoran (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. In this paper we present our modification of the Ponseti method which we have been using for the treatment of severe forms of congenital clubfoot since 2007. The aim of this paper was to determine, on the basis of the analysis of results, the impact of the early tenotomy of the Achilles tendon on the length and results of treatment of severe forms of congenital clubfoot. Methods. The study was prospective and lasted from 2007 to 2016 year. It was implemented in the Clinic for Children’s Surgery Banjaluka. The Group 1 consisted of the subjects treated by the modified Ponseti method in the period of 9 years (2007–2016). There were a total of 30 subjects (52 feet). There were 20 (67%) of male and 10 (33%) of female subjects. There were 22 (77%) subjects with bilateral and 8 (27%) with unilateral deformity. The Group 2 consisted of the subjects treated by the classic Ponseti method in the period of 9 years (2007–2016). There were a total of 32 subjects (52 feet). There were 26 (81%) of male and 6 (19%) of female subjects. There were 20 (63%) of subjects with bilateral and 12 (37%) with unilateral deformity. We used the Pirani score for: classification of deformity according to the severity, monitoring of results of the correction, determination of indication for tenotomy of the Achilles tendon and for the analysis of results of the treatment. Results. The total length of treatment in the Group 1 was from 6 to 9 weeks (mean = 6.71 ± 0.871), and in the Group 2 from 9 to 12 weeks (mean = 9.92 ± 0.882) (r = 0.86; p = 0.001). There was no difference in the results of the treatment (χ2 = 2.372 df = 2 n = 52 p = 0.936. Conclusion. Applying early tenotomy of Achilles tendon in the treatment of severe forms of congenital club foot significantly shortens the duration of treatment and has no negative impact on the results of treatment.